Acute Kidney Injury in Deceased Organ Donors: Risk Factors And Impacts on Transplantation Outcomes - Jakubov, Katarina; Petr, Vojtech; Zahradka, Ivan; Girmanova, Eva; Hruba, Petra; Keleman, Roman; Viklicky, Ondrej (Transplantation direct, 2024)
BACKGROUND: Acute kidney injury in deceased donors (D-AKI) is one of the common causes of donor kidney discard. The risk factors for D-AKI and its impact on kidney transplantation outcomes are not yet fully understood. METHODS: This single-center, retrospective cohort study included 388 donors referred between June 2021 and December 2022. D-AKI was defined and staged according to kidney disease: Improving global outcomes criteria, and donor clinical variables were analyzed to identify risk factors for D-AKI. Delayed graft function and estimated glomerular filtration rate (eGFR) at 6 mo were evaluated in 369 kidney grafts transplanted from donors with and without D-AKI. RESULTS: AKI was present in 171 deceased donors (44.1%), with 117 (30.2%) classified as AKI stage 1 and 54 (14%) as AKI stages 2 or 3. Donor history of hypertension (odds ratio [OR] 1.93; 95% confidence interval [CI], 1.21-3.10; P = 0.005), history of diabetes (OR 2.2; 95% CI, 1.21-3.98; P = 0.008), and anoxia as the cause of death (OR 2.61; 95% CI, 1.5-4.61; P < 0.001) were independently associated with an increased risk of D-AKI. Multivariable mixed models identified donor age (β -0.49; 95% CI, -0.71 to -0.28; P < 0.001) as the only independent risk factor for lower eGFR at 6 mo. D-AKI was not associated with delayed graft function or lower eGFR at 6 mo. CONCLUSIONS: Hypertension, diabetes, and anoxia as the cause of death were identified as risk factors for AKI in deceased donors. D-AKI should not be used as the sole criterion to assess the risk of poor graft outcomes. A broader range of donor variables should be considered when evaluating graft viability.